Kelimpahan dan Keanekaragaman Makrozoobentos di Sungai Bone dan Sungai Bolango Provinsi Gorontalo - Mbuinga, Adeliya; Sahami, Femy Mahmud; Kasim, Faizal; Kadim, Miftahul Khair; Habibie, Sitty Ainsyah (Jurnal Inovasi Global, 2025)
The Bone River faces potential pollution due to human activities around it. To ensure this, macrozoobentos are used as bioindicators by utilizing the characteristics of their constituent communities that exhibit sedentary behavior, limited mobility, and sensitivity to aquatic conditions. This study aims to examine the abundance and diversity of macrozoobentos in the Bone River and Bolango River, Gorontalo Province. The research was conducted from May to August 2023 at several observation stations on both rivers. The identification results showed a total of 127 macrozoobentos individuals consisting of 72 individuals in the Bone River and 55 individuals in the Bolango River, with the dominance of the Baetidae (PlatyBaetis) and Hydropsychidae (Cheumatopsyche and Hydropsyche) families that are widespread in both locations. A low dominance index indicates the absence of a single species that dominates significantly, while the fairly diverse distribution of taxa reflects relatively good water quality conditions in both rivers. These findings serve as an important basis for the sustainable monitoring and management of aquatic resources in the region.